2015
DOI: 10.1111/1744-7917.12179
|View full text |Cite
|
Sign up to set email alerts
|

Differentially methylated genomic fragments related with sexual dimorphism of rice pests, Sogatella furcifera

Abstract: Sogatella furcifera (Hovarth) is a major rice pest with sexual dimorphism. The objective of the current research was to monitor differentially cytosine methylation at CCGG sequences in male and female adults of S. furcifera to determine the association between gene methylation and sexual phenotypes using methylation-sensitive representational difference analysis. After the second subtractive hybridization, four differentially methylated DNA bands were obtained and sequenced. Ten different fragments were found.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The regulations of epigenetic mechanisms have not yet been exploited, except in a few studies, for instance, fecundity in N. lugens was sharply lowered after knockdown of Dnmt1 [ 87 ]. Similarly, sexual phenotypic variations in S. furcifera were also related to DNA methylation [ 88 ]. The presence of a higher number of opsins (17) as compared to other insects, namely, mosquitoes, contain 8–9 [ 89 ]; T. castaneum contains only two; and D. melanogaster contains seven [ 76 , 90 ], and the presence of unique long-wavelength opsin gene in YSB determines its specificity in the visual mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The regulations of epigenetic mechanisms have not yet been exploited, except in a few studies, for instance, fecundity in N. lugens was sharply lowered after knockdown of Dnmt1 [ 87 ]. Similarly, sexual phenotypic variations in S. furcifera were also related to DNA methylation [ 88 ]. The presence of a higher number of opsins (17) as compared to other insects, namely, mosquitoes, contain 8–9 [ 89 ]; T. castaneum contains only two; and D. melanogaster contains seven [ 76 , 90 ], and the presence of unique long-wavelength opsin gene in YSB determines its specificity in the visual mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese white shrimp, Fenneropenaeus chinensis , tissue-specific DNA methylation was observed (He et al, 2015 ). Furthermore, DNA methylation has been reported in many insect species of various orders including Diptera, Hemiptera, Hymenoptera, Lepidoptera, Coleoptera, Odonata, and Orthoptera (Field et al, 2004 ; Richards et al, 2008 ; Walsh et al, 2010 ; Xiang et al, 2010 ; Zhang J. et al, 2015 ; Zhang M. et al, 2015 ). In general, methylation levels of invertebrate CpG sites are relatively low, ranging from 0.36–20% (Regev et al, 1998 ), compared to mammalian systems where 60–90% of all CpG dinucleotides are subject to methylation (Suzuki and Bird, 2008 ).…”
Section: Gene Regulation Via Epigenomic Mechanismsmentioning
confidence: 99%
“…The effect of climate change and other environmental factors can cause heritable epigenetic modifications in insects, enabling a rapid evolution [ 10 ]. In hemipteran insects, including BPH, DNA methylation has been reported to be a crucial epigenetic modification in regulating several physiological processes [ 11 , 12 ]. A recent study has reported that the heritable epigenetic modifications, particularly the stress-induced DNA methylation in BPH, contributed to overall stress resilience and rapid adaptions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%